Ideations of social sustainability? Concepts and cleavages of cohesion in Germany - Marej, Katarina (Frontiers in Political Science, 2023)
The UN 2030 Agenda calls for the development and promotion of societies that pursue not only ecological and economic, but also socio-political sustainability goals. Yet, the political as well as academic discourse on that is marginal. Conducting an empirical case study in Germany, this article examines existing political ideations about societal integration and thus cohesion and discusses ideational obstacles to the development of a socially sustainable society. First, the concept of ideations is made accessible for empirical analysis by distinguishing cognitive and affective elements with symbolic, sentimental, programmatical and ideological foundations. The focus is not on the implementation of specific policies, but on the negotiation processes of the ideational foundations of integration governance. The following critical discourse analysis elaborates central aspects of ‘constitutional patriotism' and ‘Leitkultur.' It traces their emergence and characteristics and thereby reveals how different historical contexts and political interests of the actors influence the emergence and dissemination of ideations. Furthermore, it demonstrates how formerly opposing positions converge, emphasizing the impact of ideational processes on changing governance trends. Subsequently, inherent elements of cultural racism and hegemony, religion and ‘values,' and emotion politics are critically discussed as obstacles to developing decolonial ideations about integration. Accordingly, the widespread appreciation of patriotism and national pride as a foundation for successful integration is questioned. The conclusion diagnoses that republican elements are gaining influence with the tendency to individualize, paternalize, and depoliticize integration. Shared cognitive and emotional ideations are intended to ensure support for democracy, but the extent to which these policies themselves exhibit undemocratic tendencies must be critically observed. The two ideations examined are therefore not or only partially suitable for promoting social sustainability.